Greening the city : urban landscapes in the twentieth century - Brantz, Dorothee; Duempelmann, Sonja (Book collections on Project MUSE., 2011)
The modern city is not only pavement and concrete. Parks, gardens, trees, and other plants are an integral part of the urban environment. Often the focal points of social movements and political interests, green spaces represent far more than simply an effort to balance the man-made with the natural. A city's history with--and approach to--its parks and gardens reveals much about its workings and the forces acting upon it. Our green spaces offer a unique and valuable window on the history of city life. The essays in Greening the City span over a century of urban history, moving from fin-de-siècle Sofia to green efforts in urban Seattle. The authors present a wide array of cases that speak to global concerns through the local and specific, with topics that include green-space planning in Barcelona and Mexico City, the distinction between public and private nature in Los Angeles, the ecological diversity of West Berlin, and the historical and cultural significance of hybrid spaces designed for sports.--From publisher description.